Scaling whole-farm innovation bundles for sustainable and equitable mixed farming systems in Malawi - Homann-Kee Tui, Sabine; Sseguya, Haroon; Tufa, Adane; Manda, Julius; Liben, Feyera; Omondi, John Okoth (International Center for Tropical Agriculture (CIAT), 2025)
This report documents the outcomes of a national multi-stakeholder workshop convened to co-design integrated, scalable innovation bundles addressing structural constraints faced by smallholder farmers in Malawi. Participants included government ministries and departments, research institutions, development partners, financial service providers, NGOs, farmer-based organizations, and private sector actors. The workshop responded to growing evidence that isolated technical interventions have limited impact when deployed without complementary market, finance, governance, and advisory system strategies. The workshop pursued three objectives: (i) to consolidate a shared understanding of bundling approaches already applied in Malawi; (ii) to identify binding constraints limiting adoption and scale; and (iii) to co-design innovation bundles responding to farmer heterogeneity and local conditions. Discussions focused on two complementary bundles: a farm-level whole-farm integration bundle linking crops and seed systems, soil health, livestock and forages; and a landscape-level bundle anchored in Integrated Catchment Management (ICM). A central outcome was agreement on the core drivers of scale. At farm level, functional and inclusive markets were identified as the primary entry point for unlocking investment in productivity, quality, finance, and advisory services. At landscape level, ICM was confirmed as the organizing framework for integrating land, water, forestry, livestock, and local governance. Participants identified key constraints to scale, including weak aggregation and quality assurance, insecure land and water governance, misaligned financial products, fragmented extension systems, and limited enforcement of by-laws. The workshop produced an initial national roadmap for advancing whole-farm bundling in Malawi. The roadmap adopts a phased approach—foundation, learning, and institutionalization—and assigns clear institutional leadership. The Department of Agricultural Extension Services was identified as lead for the farm-level bundle, and the Department of Land Resources Conservation for the ICM bundle, working through multi-actor partnerships. Priority next steps include establishing bundle working groups, selecting 3–4 learning districts, harmonizing extension and market tools, and initiating pilots linked to existing national programs.